2019
DOI: 10.1209/0295-5075/127/39002
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach for deducing the mass composition of cosmic rays from lateral densities of EAS particles

Abstract: A Monte Carlo (MC) simulation study of cosmic ray (CR) extensive air showers (EAS) has been carried out in the energy regime of the KASCADE experiment. From the characteristics of lateral distributions of electrons and muons of simulated EAS, some important EAS observables are extracted by a novel approach, and their CR mass-sensitivity is demonstrated. The study takes into account the issue of the experimental lateral density profiles of EAS electrons and muons after introducing the notion of the local age an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Instead of taking multiple local ages belonging to a shower, a systematically chosen single age parameter was found appropriate to deal with some important issues such as composition, energy etc. on the PCRs [5,[7][8]. The minimum value of the LAP that was noticed at a particular radial distance between the first and the second maxima in the s local versus r curves appears very effective in several recent works [7][8].…”
Section: Elements Of the Simple Analytical Approachmentioning
confidence: 87%
See 4 more Smart Citations
“…Instead of taking multiple local ages belonging to a shower, a systematically chosen single age parameter was found appropriate to deal with some important issues such as composition, energy etc. on the PCRs [5,[7][8]. The minimum value of the LAP that was noticed at a particular radial distance between the first and the second maxima in the s local versus r curves appears very effective in several recent works [7][8].…”
Section: Elements Of the Simple Analytical Approachmentioning
confidence: 87%
“…The minimum value of the LAP that is assigned to a shower, is discussed below. Let us recall the feature of the LAP from both the simulations and observations in recent works [5,[7][8]. It was found that the parameter or the LDD of shower electrons exhibits some kind of scaling behavior if one studies the variation of the parameter with the radial distance from the EAS core [5].…”
Section: Elements Of the Simple Analytical Approachmentioning
confidence: 98%
See 3 more Smart Citations